Dry Rot Caused by the Complex Colletotrichum falcatum and Thielaviopsis paradoxa Emerges as a Key Stalk Disorder in Newly Expanded Sugarcane Plantations from Northwestern São Paulo, Brazil - Silva, Tatiane Carla [UNESP]; Moreira, Silvino Intra [UNESP]; Felizardo, Lucas Menezes [UNESP]; Martins, Renan Milani; Suzuki, Aline Namie [UNESP]; Faria, Gláucia Amorim [UNESP]; Montanari, Rafael [UNESP]; Ceresini, Paulo Cezar [UNESP] (MDPI, 2023)
Sugarcane dry rot emerged as an important stalk disorder in newly expanded plantations in northwestern São Paulo, Brazil, under the current no-burning fully mechanical harvest policy gradually implemented in the past 20 years. This emergence was probably due to a considerable increase in both pathogen inocula and insect pest populations in sugarcane crop residues kept in the field. In this study, we surveyed the incidence of three stalk-related disorders in commercial sugarcane fields in six municipalities in northwestern São Paulo and the corresponding yield losses. The three stalk-related disorders surveyed were as follows: the red rot disease caused by the fungal pathogen Colletotricum falcatum, the spittlebug-induced shoot stunting, and the stem dry rot, which is associated with the simultaneous infection of C. falcatum and Thielaviopsis paradoxa, the pineapple set rot pathogen. Red rot disease was detected in 88.2% of the fields surveyed, while the spittlebug-induced shoot stunting disorder and the internal stem dry rot were found in 97.1% of the fields. Stem dry rot had the highest incidence and resulted in the highest yield losses. Total sugarcane yield losses were estimated at 20.1%, with an average of 14.2 (±3.8) t·ha−1 per field. The multiple regression model constructed to determine which of the three stem-related disorders contributed the most to total yield losses was not significant. Subsequently, the performance analyses of single-variable polynomial regression models indicated that the simple linear model was the best fit in terms of independently predicting sugarcane yield losses based on each stem-related disorder. Positive and significant correlations were only detected between sugarcane yield losses in t·ha−1 and the incidence of red rot disease or leafhopper-induced shoot stunting. We concluded that the stalk’s internal dry rot, as a disease complex associated with both C. falcatum and T. paradoxa, was the most important disorder in sugarcane fields in the northwest region of São Paulo state. A sustainable pest management program is needed to reduce the impact of all three stalk-associated disorders on regional sugarcane production.
Keywords: emerging disease; ineffective control; red rot complex; yield loss